Hierarchical shape-controlled mixed-valence calcium manganites for catalytic ozonation of aqueous phenolic compounds12. Issue 9 (15th January 2016) - Wang, Yuxian; Xie, Yongbing; Sun, Hongqi; Xiao, Jiadong; Cao, Hongbin; Wang, Shaobin
Abstract : Catalytic ozonation has attracted intensive attention due to its efficient degradation of various organic pollutants in water. Abstract : Catalytic ozonation has attracted intensive attention due to its efficient degradation of various organic pollutants in water. The key to a practical application is the discovery of highly effective catalysts. This study, for the first time, reports excellent performances of porous mixed-valence calcium manganite (CaMn3 O6 and CaMn4 O8 ) microspheres made of 1D nanorods in the catalytic ozonation of 4-nitrophenol. The CaMn3 O6 and CaMn4 O8 showed much higher activities and stabilities than manganese oxides. From a variety of advanced characterizations, the mechanism of surface catalysis was discussed in detail. Quenching reagents and electron paramagnetic resonance (EPR) spectroscopy were applied to probe the dominant reactive species in the catalytic ozonation over the calcium manganites. It was found that superoxide radicals and singlet oxygen rather than hydroxyl radicals contributed to the degradation and mineralization of 4-nitrophenol. Moreover, the effects of electron-withdrawing groups (EWG) and electron-donating groups (EDG) in the phenolic compounds on the ozonation/catalytic ozonation over the calcium manganites were investigated using phenol, p -cresol and p -chlorophenol as target pollutants.